(untitled) (Journal of Global Arts Studies, 2024)
Background: This study examines the construction and dissemination of female imagery in tea packaging and posters during the Republican Era (1912-1949). It explores how these images were represented in commercial visual language and their cultural significance during this unique historical period. Objective: The aim is to reveal the role of these images in brand positioning, marketing, and cultural communication. Methods: Through literature review and case analysis, the study investigates the representation forms, visual design elements, and their impact on brand communication. Results: Various types of female imagery not only enhanced the visual appeal of tea packaging but also conveyed rich cultural connotations, reflecting brand positioning and value propositions. Conclusion: The female imagery in tea packaging during the Republican Era not only enriched the expression of visual art but also served as a crucial bridge connecting traditional culture and modern commerce, providing valuable insights for contemporary tea packaging design.